2019
DOI: 10.1002/jgh3.12169
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the outcome between alcohol and gallstone pancreatitis in a high‐volume tertiary care center

Abstract: Background and Aim The two most common etiologies of acute pancreatitis (AP) are alcohol and gallstone. Whether etiology contributes to the outcome in patients with AP is an unresolved issue, more so in the severe form of the disease. The aim is to study the effects of the etiological factors of alcohol and gallstone on the disease course and the role of etiology in the subgroup of severe AP. Methods Consecutive patients of AP with alcohol or gallstone etiology were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…It is the most common gastrointestinal cause of hospitalization [1], associated with high financial burdens [2]. Several studies have shown that the incidence of AP is increasing [3,4], probably as a result of a combination of risk factors, such as obesity and gallstone disease [5]. The overall mortality rate is 3% to 10%, but patients with the severe form of the disease are at an increased risk of death, with a mortality rate of 36% to 50% [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the most common gastrointestinal cause of hospitalization [1], associated with high financial burdens [2]. Several studies have shown that the incidence of AP is increasing [3,4], probably as a result of a combination of risk factors, such as obesity and gallstone disease [5]. The overall mortality rate is 3% to 10%, but patients with the severe form of the disease are at an increased risk of death, with a mortality rate of 36% to 50% [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The overall mortality rate is 3% to 10%, but patients with the severe form of the disease are at an increased risk of death, with a mortality rate of 36% to 50% [2,6,7]. Although its etiology is complex and not known for certain, the two most common causes are gallstones and alcohol [3,8]. Numerous studies have been published about the pathogenesis of AP; however, the precise mechanism behind this pathology remains unclear [9].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, there was no significant difference in all-cause in-hospital mortality between patients with AAP and ABP (aOR 0.95, 95%CI 0.69-1.31; P=0.79). Multiple studies have reported a similar absence of mortality difference between the 2 groups [ 8 , 13 , 20 ]. However, some studies reported a more severe course and higher mortality in the alcohol group [ 11 , 12 ], while other, older studies reported a more severe outcome in the biliary group [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 74%
“…However, it is pertinent to remember that, while statistically significant, the differences in some of these outcomes were quite modest and indicate a somewhat similar clinical course between the 2 groups. There have been previous studies comparing the outcomes of alcohol-induced and gallstone pancreatitis in patients admitted to tertiary centers, but the sample size was in the hundreds [ 20 , 21 ]. In comparison, we were able to look at 553,480 adult patients with AP across the nation, including 140,195 (25.3%) with AAP and 96,540 (17.44%) with ABP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation